2022
DOI: 10.3390/sports10050064
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adaptations to High-Intensity Interval Training in Overweight and Obese Adults: A Topical Review

Abstract: Regular exercise has been reported as a fundamental piece of the management and treatment puzzle of obesity, playing a vital role in numerous psychological indicators. However, it is unclear whether high-intensity interval training (HIIT) can improve critical psychological health markers such as adherence, exercise enjoyment, affective responses, health-related quality of life, anxiety, and depression in overweight and obese adults. The purpose of this topical review was to catalogue studies investigating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 104 publications
1
17
0
1
Order By: Relevance
“…Studies have shown interval aerobic training to be a more enjoyable or as enjoyable form of exercise compared to continuous aerobic training. Positive psychological outcomes have been reported among sedentary obese women after participation in interval exercise; however, many of these studies employed moderate-intensity continuous training (MICT) in comparison to HIIT, with minimal attention paid to moderate-intensity interval training (MIIT) [7][8][9][10][11]. MICT typically involves continuous aerobic workloads of 40-60% VO 2 Reserve or heart rate reserve, a 12-13 on the Borg rating of perceived exertion (RPE) scale (scaled [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], or an equivalent of 3-5.9 METs [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown interval aerobic training to be a more enjoyable or as enjoyable form of exercise compared to continuous aerobic training. Positive psychological outcomes have been reported among sedentary obese women after participation in interval exercise; however, many of these studies employed moderate-intensity continuous training (MICT) in comparison to HIIT, with minimal attention paid to moderate-intensity interval training (MIIT) [7][8][9][10][11]. MICT typically involves continuous aerobic workloads of 40-60% VO 2 Reserve or heart rate reserve, a 12-13 on the Borg rating of perceived exertion (RPE) scale (scaled [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], or an equivalent of 3-5.9 METs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Positive psychological outcomes have been reported among sedentary obese women after participation in interval exercise; however, many of these studies employed moderate-intensity continuous training (MICT) in comparison to HIIT, with minimal attention paid to moderate-intensity interval training (MIIT) [7][8][9][10][11]. MICT typically involves continuous aerobic workloads of 40-60% VO 2 Reserve or heart rate reserve, a 12-13 on the Borg rating of perceived exertion (RPE) scale (scaled [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], or an equivalent of 3-5.9 METs [12]. MIIT requires similar workloads to MICT, but is broken up into interval bouts, similar to HIIT.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to explain the popularity of the aforementioned trends related to fitness activities from a scientific standpoint, a large and convincing body of evidence reveals that a HIIT may be an injury-free, efficient, time-effective, and enjoyable type of exercise for improving metabolic health, physical fitness, and well-being in populations with unhealthy weight representing the vast majority of the adult population worldwide nowadays [30][31][32]. Additionally, emerging research demonstrates that hybrid-type exercise programs incorporating HIIT, functional fitness and body weight training into a single session performed in a small-group setting induce positive alterations in various psychophysiological markers [33][34][35][36][37] among overweight and obese populations.…”
Section: What Is Trending In Fitness Activities?mentioning
confidence: 99%
“…However, such a time-consuming exercise strategy [ 19 ] demonstrates high dropout and low adherence rates among adults with overweightness and obesity [ 20 ]. On the other hand, high-intensity interval training appears to be a time-efficient [ 21 , 22 ] and popular [ 23 ] exercise type, but such a demanding approach is not clearly feasible and attractive to populations that are overweight and obese [ 24 ] given that lack of time has been reported as a major barrier to exercise among adults [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%